Epistolario, Vol. 2, maggio 1922-novembre 1923, a cura di Davide Bidussa, Francesco Giasi e Maria Luisa Righi (in italiano) - La Porta, Lelio (International Gramsci Journal, 2023)
Gramsci’s correspondence January-November 1923 includes both political letters (to and from him, a number published here for the first time) and also personal ones, some redated and, in consequence, having as recipient not the Schucht sister (Julija) to whom they were until recently thought to be addressed. The background information supplied to the political letters, and inclusion in the volume of the letters received by Gramsci, helps to flesh out the general context of what was happening in both the Comintern and in the Italian Communist Party. In the aftermath of the Fourth Congress of the International (November-December 1922) a clarification of positions began in the PCI, with what would become the centre group around Gramsci distancing itself both from Bordiga’s left and from Tasca’s right (later incorporated into the centre). Further, under pressure from the International, moves – not accepted by everyone – began towards a stable alliance between the infant Communist Party and the pro- Comintern left of the Socialist Party (the Third Internationalist fraction); after the last relatively free elections, the majority of this fraction then merged with the PCI into what became a united Communist Party.